Treatment of o-tert-Butyl Phenol Micro-Polluted Water with Electro-Oxidation and Microporous Aeration: Method Development, Performance Evaluation and Mechanism Study - Chen, Z. (Asian Journal of Chemistry, 2015)
This study investigated the treatment of organic micro-pollutants in drinking water using a combination of electro-oxidation and microporous aeration (EOMA) technique. Results indicated that microporous aeration enhanced the turbulence of reaction solution and improved the efficiency of organic contaminant removal two-fold versus electro-oxidation alone. o-tert-Butyl phenol (OTBP) was used as a representative pollutant. 1600 mL OTBP solution contained 160 mg sodium sulfate and 2 mL 30 % hydrogen peroxide. When the current density was 5 mA cm-2, 1 and 2 mg L-1 o-tert-butyl phenol was removed up to 98.0 and 75.1 %, respectively. The major intermediate products included trimethylacetic acid, succinic acid and other acid. These have much less toxicity than o-tert-butyl phenol. After 30 min, the organics were mineralized completely. Electro-oxidation and microporous aeration was applied to actual source water that was contaminated by complicated organics. No toxicity was shown to algae growth after 15 min of treatment and total organic carbon was removed completely after 30 min.